Uso do concentrado proteico de soja para frangos de corte de 1 a 21 dias de idade - Vasconcelos, Luciana Guimarães (2014)
Two experiments to evaluate the effect of the use of soy protein concentrate (SPC) in the diet of broilers from one to 21 days of age were performed. In the first experiment 600 broiler, males, of Cobb, from one to 40 days of age, were distributed in a completely randomized design (CRD) with four treatments, six replicates and 25 birds per experimental unit. Treatments consisted of four levels of inclusion of soy protein concentrate (0, 30, 60 and 90 g/kg) levels of pre-starter and starter diets. The parameters evaluated were: performance, enzyme production in the pancreas, gut integrity and immune parameters. In the second experiment, 144 broilers, males, of Cobb, from one to 21 days of age, distributed in CRD with four treatments, six replicates, and six birds per experimental unit. These birds were fed with experimental diets from 14 to 21 days of age and total excreta, to review the metabolization of rations, collected from 18 to 21 days old. The treatments were the same as in the first experiment. The results were submitted to ANOVA and Scott-Knott test; the polynomial regression; the nonparametric analysis (Kruskal-Wallis) and Bonferroni test; adopted was α = 0.05. The use of 30 and 90 g/kg SPC did not affect the weight gain, feed intake, feed conversion or the viability of the poultry. The use of 30 and 60 g/kg of SPC in the diet increased the activity of trypsin and the use of 90 g/kg increased amylase activity. The villus length and crypt depth in the small intestine increased with the use of 60 and 90 g/kg of SPC in the diet and the villous:crypt of the jejunum increased in the absence of SPC. The total leukocytes, eosinophils and lymphocytes and the dosage of immunoglobulin A (IgA) serum levels were not influenced by the SPC proposed in this study. The metabolization coefficient of dry matter (CMMS) increased linearly with the addition of SPC, although the metabolization coefficient of ash (CMCz) has reduced linearly.